A clinical case of a patient with congenital heart defect and a pacemaker dysfunction - Hafeel, Aysha; Liudmila, Kalatsei; Shafran, U. Mohamed; Thilakarathna, Nethmi Ramalka (International Journal of Research in Medical Sciences, 2025)
Ebstein anomaly (EA) is a congenital heart defect characterized by malformation of the tricuspid valve, leading to various cardiovascular complications, including arrhythmias and heart failure. This case report presents the clinical journey of a 33-year-old female patient with a complex medical history, including congenital heart disease (EA) and multiple interventions related to her cardiac condition, including a mechanical tricuspid valve prosthesis. Following a recent dual-chamber pacemaker implantation, the patient experienced acute episodes of sharp, electric shock-like pain in the epigastric region, and X-ray imaging revealed dislocation of the atrial electrode. Re-implantation of the atrial electrode was performed; however, the postoperative period was marked by fluctuations in the patient’s condition. A multidisciplinary team involving cardiologists, clinical pharmacologists, and cardiothoracic surgeons was assembled to manage her care. The patient’s recovery trajectory showed positive dynamics, with stabilization of her symptoms and resolution of pleural effusions over time.